2018
DOI: 10.1088/2057-1976/aae02e
|View full text |Cite
|
Sign up to set email alerts
|

Track structure simulation of low energy electron damage to DNA using Geant4-DNA

Abstract: Due to the physical and chemical processes that are involved, interactions of ionizing radiations with cells lead to single-and double-strand breaks (SSB and DSB) and base damage to DNA cells. The damage may kill the cells or may be mis-repaired and lead to genetic diseases and cancers. Track structure Monte Carlo simulation of the DNA damage provides types of the damage and their frequencies. In the present work, to derive initial DNA damage, we used the Geant4-DNA code to simulate the physical, physico-chemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Analysis of the yield results of Table 2 shows that Y SSB / Y DSB increased linearly with primary energy as 0.0085/MeV or equivalently as 0.1025/(MeV/u). This can be compared with similar results for primary alphas, protons, and electrons—shown in Moeini et al., 17 and Mokari et al 16,48 . to increase with primary energy almost linearly as 0.35, 0.78, and 4320.7/MeV, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Analysis of the yield results of Table 2 shows that Y SSB / Y DSB increased linearly with primary energy as 0.0085/MeV or equivalently as 0.1025/(MeV/u). This can be compared with similar results for primary alphas, protons, and electrons—shown in Moeini et al., 17 and Mokari et al 16,48 . to increase with primary energy almost linearly as 0.35, 0.78, and 4320.7/MeV, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, a threshold of 17.5 eVcalculated by Martin and Haseltine 46 through modeling the experimental data of 125 I and confirmed later by Kandaiya et al 47 through substantial analyses-was to be satisfied for registering an SB as a direct damage. For an SB to be registered as indirect damage caused by chemical reactions, a probability of 0.13 was assumed 42,48 -provided that a hydroxyl radical could, within 1 ns of its production in water, 49 approach as close as 4 + 1.15 nm to the axis of a sampled DNA with 1.15-nm cross-sectional radius. The yield values were calculated based on the method discussed by Charlton et al as…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, complex DNA damage composed of at least three vicinal lesions caused within 10-20 bp, such as DSBs coupled with strand breaks or base damage (BD), is believed to be more lethal to cells than simple DSBs [20,21] due to refractory damage [22,23]. To assess lethality, it is necessary to quantify the clustering degree of DNA damage with both experiments [24,25] and simulations [8,[26][27][28][29]. It has been pointed out that a considerable amount of complex DNA damage can be induced after irradiation; however, the yield and nature of complex DNA damage are still difficult to be experimentally measured [30].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [36] demonstrated a 2% decrease in survival rate using a 3 MeV proton beam irradiating EMT-6 murine breast carcinoma cells and 12% of CT26 mice colorectal adenocarcinoma cells while using GNPs. Recently, Mokari et al [43,44] has performed simulation of proton interaction with DNA in a wide energy range. They have calculated direct and indirect damages of DNA due to proton interaction and chemical species using Geant4-DNA.…”
Section: Jinst 17 P05034mentioning
confidence: 99%